Highly Durable Piezoelectric Nanogenerator by Heteroepitaxy of GaN Nanowires on Cu Foil for Enhanced Output Using Ambient Actuation Sources. Issue 47 (15th October 2020) - Johar, Muhammad Ali; Waseem, Aadil; Hassan, Mostafa Afifi; Bagal, Indrajit V.; Abdullah, Ameer; Ha, Jun‐Seok; Ryu, Sang‐Wan
Abstract: Highly durable piezoelectric nanogenerators (PENGs) with high conversion efficiency and high power density are of great interest. Here, a foldable, scalable, durable, cost‐effective, sensitive, and high current output PENG developed by the direct integration of van der Waals heteroepitaxial growth of GaN nanowires (NWs) by metal‐organic chemical vapor deposition using a graphene coating on a Cu‐foil is reported where the direct growth of GaN on the metallic substrate plays a key role in achieving the high stability of the PENG. The PENG provides a durable and highly sensitive output compared to the previously reported GaN NW‐based PENGs fabricated by transferring NWs onto a foreign substrate. The reported PENG can harvest energy from a variety of ambient actuation sources such as bending, vibrations, air flow, finger pressing, foot striking, fluid flow, and normal force by weights, with the maximum piezoelectric output voltage and current density recorded as 19.7 V and 1.9 mA cm −2, respectively. Due to its high conversion efficiency, the PENG can power several LEDs and thus can be used to power electronic devices. More importantly, the PENG retains its performance after more than 4 million actuation cycles, demonstrating the potential of the design for practical applications using biomechanical and ambient actuation sources for self‐powered systems. Abstract : Heteroepitaxial growth of single crystal GaN nanowire on graphene‐coated Cu‐foil is performed by metal‐organic chemical vapor deposition for piezoelectric nanogenerator applications to scavenge biomechanical and ambient energy using actuation sources such as normal weights, bending by a cyclic stretching–releasing agitation mechanism, vibrations, finger pressing, foot striking, air‐breathing, wind, and fluid pressure. Additionally, the device stability is evaluated for more than 4 million actuation cycles.